Refusal to eat: a century of prison hunger strikes - Shah, Nayan (University of California Press, 2022)
Suffragists and the shaping of the hunger striking form -- The medical ethics of forcible feeding and a brief history of four objects -- Irish republicans innovating hunger strikes for anti-colonial rebellion -- Gandhi's fasts, prisoner hunger strikes, and Indian independence -- Solidarity and survival at Tule Lake stockade -- South African anti-apartheid hunger strikes -- Controversies of medical intervention in Northern Ireland -- Biomedical technologies, medical ethics, and the management of hunger strikes -- Australian refugee detention, trauma, and mental health crisis -- Captives in U.S. detention and their networks of resistance and solidarity.